Deep Learning Based Sentiment Analysis: A Survey - Singh, Lakhan; Agrawal, Chetan; Meena, Pawan (International Journal of Computer Sciences and Engineering, 2024)
Sentiment analysis, a pivotal area within natural language processing, has witnessed significant advancements with the advent of deep learning methodologies. This survey provides a comprehensive overview of the state-of-the-art in sentiment analysis, focusing specifically on the application of deep learning techniques. The aim is to present a thorough exploration of the existing literature, methodologies, and challenges associated with leveraging deep neural networks for sentiment analysis tasks.